2011
DOI: 10.1007/s10620-010-1538-1
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Outcome of Colonoscopy in the Middle of Nile Delta of Egypt

Abstract: In Egyptian patients subjected to colonoscopy, the most frequent diagnoses were UC, followed by hemorrhoids, CRC, benign polyps, and CD. This may represent an increasing incidence of UC and CRC. Colonoscopy was safe and few complications were recorded. Prospective population-based studies are needed in order to measure the incidence, prevalence, and risk factors of various diseases of the colon in Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 9 publications
3
33
1
Order By: Relevance
“…This confirms that inflammatory bowel disease IBD is still rare in Nigeria with few reports of sporadic cases [18,19]. However, in Nile Delta, Egypt, IBD has been reported in 25% of cases, haemorrhoids 18% and diverticulosis 2% [11]. Surprisingly, diverticular disease, which is more common to western population attributable to a low residue diet pattern, was the 3rd leading pathology recorded in our metropolitan study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This confirms that inflammatory bowel disease IBD is still rare in Nigeria with few reports of sporadic cases [18,19]. However, in Nile Delta, Egypt, IBD has been reported in 25% of cases, haemorrhoids 18% and diverticulosis 2% [11]. Surprisingly, diverticular disease, which is more common to western population attributable to a low residue diet pattern, was the 3rd leading pathology recorded in our metropolitan study.…”
Section: Discussionsupporting
confidence: 77%
“…Some studies from different parts of Nigeria have reported diagnostic yield between 70% to 80% [9,10]. In Egypt and Iran, reports of 72% and 65% diagnostic yield respectively have been recorded for colonoscopy [11,12]. Across Europe, significant pathologies (cancer, adenomatous polyps, angiodysplasia, and new diagnoses of inflammatory bowel disease) is reported in 25% of colonoscopies [13].…”
Section: Discussionmentioning
confidence: 99%
“…3033 To date, this finding has not been tied to race. However, we found that non-Caucasian participants had a 26% lower risk than Caucasians even after adjustment for risk factors.…”
Section: Discussionmentioning
confidence: 94%
“…The epidemiological characters of IBD in Egypt is similar to those in Asian and African population with UC/CD ratio of 6:1. The incidence in Egypt has increased in the past ten years [5,6].…”
Section: Introductionmentioning
confidence: 99%